Zasady kontroli jako szczególne zasady prawa regulujące funkcjonowanie systemu kontroli - Murat, Leszek (Kwartalnik Prawa Publicznego, 2017)
Out of various principles of law, principles of audit law belong to the least examined. Although jurisprudence identified over forty audit law principles, only a few of them have been defined. In the article, I discuss functioning of audit law principles, their relations to values as well as commonality of their observance among auditors. I enrich my arguments by results of a survey I conducted in 2015 among employees of two audit institutions. It reveals that principles of audit law gained general respect and that auditors expect them to be more useful in the future.